Sistem Pengendalian dalam Ekonomi dan Manajemen - Tatik Budiningsih (Jurnal Manajemen Maranatha, 2003)
The principal of the control system is to manage a system in such way hence the result of that system can be measured and compared with the expected result standard. If they were some discrepancies, a correction should be made to rectify the discrepancies according to the expected requirement.In social system, management, economics and cooperation forinstance, control system is a required function in order to operate the system in such arrangement in order to provide productivity as planned standard. The requirement of a reliable control system in the future 21St century is increased, because data to be processed are plenty, more complex and changes dynamically. Planning is well known in management field. It basically is a standard to be followed in order to operate a project or trading. Nowadays, computer systems have been developed and widely used; therefore cash flow control system can be programmed and implemented easilyeven though the data are relatively abundant. Similar situation in cooperation, control system is necessary, many examples proved that the achievement of the cooperation is dependenton controlling. Because its control system was not well planned, it seemed the success on the cooperation is relied on its organizer.Key words : control system, management